The semiotics of the title : a comparative and historical analysis of drug legislation - D. Manderson (Law Text Culture, 1995)
Behind the variable minutae of offences and penalties controlling the use of illicit drugs (such as the opiates, cocaine, and marijuana) around the world, there is a remarkable sameness of character and ferocity. In the Philippines and Jamaica, in Malaysia and Singapore, and in some of the United States, drug trafficking may be punishable by death. In the several States of Australia, the trafficking of a "commercial quantity" of a drug may typically lead to a penalty of 25 years' imprisonment and in addition a fine of up to $250,000. In some jurisdictions the guilty are liable to $500,000 fines and to life imprisonment. In Canada likewise, and in the United Kingdom, trafficking in a narcotic drug or even possession for that purpose are punishable by life imprisonment. As Robert Solomon and S.J. Usprich have argued in the Canadian context, the Narcotic Control Act (Can.) and its many analogues are extraordinary, not simply due to the severity of particular provisions but because so many exceptional devices are therein harnessed together. Other laws also provide for harsh penalties; for mandatory sentencing; for a reverse onus of proof, requiring defendants to prove their innocence; for expanded police powers of search and seizure: but only in 'drug' laws do all these measures coalesce. The result is that modern drug laws around the world are a collection of extravagances, an expression of fury in legislative form.